2023
DOI: 10.1158/1078-0432.ccr-22-2497
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CDKN2A Cooperates with WWTR1(TAZ)–CAMTA1 Gene Fusion to Promote Tumor Progression in Epithelioid Hemangioendothelioma

Abstract: Purpose: Epithelioid hemangioendothelioma (EHE) is a vascular sarcoma caused by the WWTR1(TAZ)-CAMTA1 (TC) gene fusion. This fusion gene has been observed in almost all reported EHE cases and functions as a constitutively activated TAZ. Sequencing of human tumors has, however, identified additional secondary mutations in approximately 50% of EHE, most commonly the loss of tumor suppressor CDKN2A. In this study, the effect of loss of CDKN2A in EHE tumorigenesis was evaluated. Design: Mice bearing a conditional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…Previous sequencing studies found secondary mutations in approximately 50% of human EHE, including key secondary variants such as CDKN2A , which can serve as a diagnostic marker for aggressive EHE 26 and is able to drive aggressive tumor behavior in a mouse model of WWTR1::CAMTA1 ‐fused EHE 6 . In our EHE patient, we also observed six secondary somatic variants including DIS3, FANCA, FUBP1, MSH3, ROS1, and SHOC2 , all of which have been linked to poor prognosis in cancer 27–32 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous sequencing studies found secondary mutations in approximately 50% of human EHE, including key secondary variants such as CDKN2A , which can serve as a diagnostic marker for aggressive EHE 26 and is able to drive aggressive tumor behavior in a mouse model of WWTR1::CAMTA1 ‐fused EHE 6 . In our EHE patient, we also observed six secondary somatic variants including DIS3, FANCA, FUBP1, MSH3, ROS1, and SHOC2 , all of which have been linked to poor prognosis in cancer 27–32 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, in a genetically engineered mouse EHE model, expression of a Wwtr1::Camta1 gene fusion in the endothelial lineage drives EHE tumor formation, recapitulating human WWTR1::CAMTA1 ‐fused EHE 5 . Subsequently, tumor‐derived EHE cell lines and EHE allograft models have been successfully established from this model 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in EHE, a recent genomic profiling study demonstrated recurrent alterations in CDKN2A/B , RB1 , APC , and FANCA , which were more common in advanced stage (III/IV) disease [64]. Further, it was shown that CDKN2A loss enhances the tumorigenicity of EHE in a genetically engineered EHE mouse model [65].…”
Section: Clinically Significant and Recurrent Secondary Genetic Alter...mentioning
confidence: 99%
“…Alternative fusions such as WWTR1 :: MAML2 and WWTR1 :: ACTL6A have been reported in rare tumours, with a predominance for cardiac involvement 188 . Genomic changes including CDKN2A loss have been implicated in tumour progression 189 …”
Section: Introductionmentioning
confidence: 99%